Longgo sebagai Sajian dalam Upacara Adat Penyambutan Tamu di Kecamatan Tolangohula - Antu, Arwin W.; Karlan, La Ode; Semiaji, Trubus; Sitharesmi, Riana Diah; Dajafar, Nurlia (Ideas Publishing, 2024)
Longgo as a dish in traditional ceremonies for welcoming guests in Tolangohula District is not yet fully understood and known by the people of Gorontalo. Based on these problems, the aim of this research is to describe the structure of Longgo presentation in the traditional ceremony of welcoming guests in Sukamakmur Village, Tolangohula District, Gorontalo Regency. This research method is qualitative research which aims to provide a detailed description of the phenomena related to the problem being studied. The results of the research show that the movements in longgo consist of three movements, including respect movements, security movements, and inviting movements.